Use of Confectionery Waste in Biogas Production by the Anaerobic Digestion Process - Pilarska, Agnieszka A. (Molecules, 2018)
It was the objective of this study to verify the efficiency and stability of anaerobic digestion (AD) for selected confectionery waste, including chocolate bars (CB), wafers (W), and filled wafers (FW), by inoculation with digested cattle slurry and maize silage pulp. Information in the literature on biogas yield for these materials and on their usefulness as substrate in biogas plants remains to be scarce. Owing to its chemical structure, including the significant content of carbon-rich carbohydrates and fat, the confectionery waste has a high biomethane potential. An analysis of the AD process indicates differences in the fluctuations of the pH values of three test samples. In comparison with W and FW, CB tended to show slightly more reduced pH values in the first step of the process; moreover an increase in the content of volatile fatty acids (VFA) was recorded. In the case of FW, the biogas production process showed the highest stability. Differences in the decomposition dynamics for the three types of test waste were accounted for by their different carbohydrate contents and also different biodegradabilities of specific compounds. The highest efficiency of the AD process was obtained for the filled wafers, where the biogas volumes, including methane, were 684.79 m(3) Mg(−1) VS and 506.32 m(3) Mg(−1) VS, respectively. A comparable volume of biogas (673.48 m(3) Mg(−1) VS) and a lower volume of methane (407.46 m(3) Mg(−1) VS) were obtained for chocolate bars. The lowest volumes among the three test material types, i.e., 496.78 m(3) Mg(−1) VS (biogas) and 317.42 m(3) Mg(−1) VS (methane), were obtained for wafers. This article also proposes a method of estimation of the biochemical methane potential (theoretical BMP) based on the chemical equations of degradation of sugar, fats, and proteins and known biochemical composition (expressed in grams).